Impact of workload and incentives on employee turnover intention: work stress as mediation - Ertanto Bio; Roby Sambung (Jurnal Inovasi Ekonomi, 2022)
This study aims to examine and explain the role of job stress in mediating the relationship between workload, incentives, and turnover intention. Samples were taken from as many as 44 employees who worked for at least 6 months. Hypothesis testing in this study using Smart PLS 3.3.3. The study's results explain that incentives have a negative effect on work stress and turnover intention, and work stress has a positive impact on turnover intention. This finding also explains that job stress is a competitive partial mediation. This study develops a model from previous studies that give different results between workload and work stress.